2005
DOI: 10.1111/j.1445-2197.2005.03574.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of intubated patients with traumatic brain injury to Auckland City Hospital

Abstract: Transfer times for brain trauma patients are currently longer than recommended for optimal neurological outcome. Referring hospitals and transfer organizations should review their systems to identify areas for improvement. Direct admission to theatre needs to be expedited within ACH when required. Triage of all trauma patients in metropolitan Auckland with a Glasgow Coma Scale score of less than 14 to ACH would be likely to improve time to treatment. A mobile acute neurosurgical service based in Auckland that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Most transfers originated from hospitals that do not have full-time emergency neurosurgery coverage. Transfer times measured from the time of diagnosis to arrival at the neurosurgery-capable hospital averaged 5.2 hours, similar to transfer times recorded in neurosurgery transfers in rural New Zealand (13). Ten percent of patients experienced a decline of greater than three points on the GCS scale during the transfer.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Most transfers originated from hospitals that do not have full-time emergency neurosurgery coverage. Transfer times measured from the time of diagnosis to arrival at the neurosurgery-capable hospital averaged 5.2 hours, similar to transfer times recorded in neurosurgery transfers in rural New Zealand (13). Ten percent of patients experienced a decline of greater than three points on the GCS scale during the transfer.…”
Section: Resultsmentioning
confidence: 96%
“…Because of concerns for delays in transfer of head injured patients in New Zealand, Lind et al (13) reported on a series of 34 patients with traumatic brain injury requiring transfer to a tertiary facility in Auckland, New Zealand. They found a median transfer time from the time of the outside facility computed tomographic diagnosis to arrival at the tertiary facility of 4.4 hours.…”
Section: Discussionmentioning
confidence: 98%
“…4,8 While most prior studies examined transfers of trauma patients. 6,7,9 our study was unique in that we included all patients transferred to the neurosurgical service, thus capturing a large number of patients transferred for neoplasms, spine-related complaints, and other non-traumatic pathology. Finally, we found that PATs were more likely to have Medicare and less likely to have private insurance, which we did not initially postulate.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, to our knowledge, investigations to identify a group of potentially avoidable transfers have yet to be performed. The aims of this study were to describe patterns of neurosurgical transfers to a tertiary care facility, identify potentially avoidable transfers, and assess the direct transportation costs of potentially avoidable transfers.…”
mentioning
confidence: 99%
“…[14] In this study only 33% of the "local" patients, and none from hospitals outside the city, arrived within 4 hours from the onset of their trauma. [15] These authors noted that there was "no special reasons for delayed transfer," and suggested that a systems-based approach among hospitals and changes to triaging protocols could impact these results [15]. This concept of streamlining and organizing transportation systems, networks, and protocols can result in improvement in transportation times and potentially in patient outcomes for defined trauma subsets [16].…”
Section: Discussionmentioning
confidence: 99%